Effect of Cryogenic Treatment Prior to Rolling on Microstructure and Mechanical Properties of AZ31 Magnesium Alloy. Issue 10 (October 2018) - Zhiquan, Huang; Jianchun, Wei; Qingxue, Huang; Lifeng, Ma; Xiangyu, Gao; Zhaohan, Yue
Abstract: The effects of cryogenic treatment prior to hot rolling on the strength, toughness and ductility of as-cast AZ31 magnesium alloy plates were investigated. The cryogenic treatment conditions were −60 °C/12 h, −120 °C/12 h, −180 °C/12 h, −60 °C/2 h, and −180 °C/2 h. Experimental results show that appropriate cryogenic treatment conditions can significantly refine the grain size and the improve strength, toughness and ductility. A large number of twins appear in both kinds of samples cryogenically treated for 2 h. The sample experienced cryogenic treatment for 12 h at −60 °C followed by rolling process shows the finest and most uniform and increase in yield strength by 25.8%. Meanwhile, a four-time increase in extension rate (3.06% to 12.31%) is attains. The tensile fracture present a mixed-mode fracture, which is characteristic of brittle and ductile fracture mechanisms.